Implications of doping and depletion on the switching characteristics in polymer-based organic field-effect transistors - Tiwari S.; Pandey M.; Takashima W.; Nagamatsu S.; Balasubramanian S.K.; Hayase S.; Pandey S.S.; Prakash R. (My University, 2025)
An effective approach for tuning the electronic characteristics of polymer-based organic field-effect transistors (OFETs) consisted of poly(3-hexylthiophene) (P3HT) doped with 7,7,8,8-tetracyanoquinodimethane (TCNQ) and depleting layer formed by aluminum (Al) coating is being reported. Doping of P3HT was employed to accumulate and tune the carrier concentration while implementation of depletion layer led to reduce the channel conductance. It has been demonstrated that on-currents in the OFETs were enhanced with the extent of TCNQ doping from 0% to 20% in the P3HT. Upon introduction of an ultra-thin Al led to the formation of depletion region resulting in to further decrease in the off-state current along with the improvement in the subthreshold characteristics. These two procedures provide counter-effects in terms of the on-state characteristics by doping and the off-state characteristics by depletion, which promotes switching performance in OFETs indicating the potentiality of doping technology for organic electronics. © 2018 Elsevier B.V.